2009
DOI: 10.1124/mol.108.054346
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modulation of mGlu2 Receptors by Histone Deacetylase Inhibitors in the Treatment of Inflammatory Pain

Abstract: Knowing that expression of metabotropic glutamate 2 (mGlu2) receptors in the dorsal root ganglia is regulated by acetylation mechanisms, we examined the effect of two selective and chemically unrelated histone deacetylase (HDAC) inhibitors, N- (2-aminophenyl)-4-[N-(pyridine-3-ylmethoxy-carbonyl)aminomethyl]benzamide (MS-275) and suberoylanilide hydroamic acid (SAHA), in a mouse model of persistent inflammatory pain. Although a single subcutaneous injection of MS-275 (3 mg/kg) or SAHA (5-50 mg/kg) was ineffecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
152
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(169 citation statements)
references
References 41 publications
10
152
0
Order By: Relevance
“…Results from transgenic mice point to mGlu2 receptors mediating the effects of the mixed agonist in models of schizophrenia (Fell et al, 2008;Woolley et al, 2008), whereas human tissue studies favor a role for mGlu3 receptors in psychiatric disease (Corti et al, 2007a;Harrison et al, 2008). The mGlu2 receptors also appear to mediate the analgesic effects of mixed agonists (Chiechio et al, 2009), whereas mGlu3 receptors mediate their neuroprotective effects (Corti et al, 2007b), and their anxiolytic activity appears to be mediated by both group II receptors (Linden et al, 2005). However, the initial behavioral observation that the insensitive B&K:Wi strain shows a more anxiety-like profile suggests that the lack of mGlu2 receptors may be one of the factors leading to an anxious phenotype and may suggest that mGlu2 receptors mediate at least some of the anxiolytic actions of mixed mGlu2/3 agonists reported in the clinic (Grillon et al, 2003;Dunayevich et al, 2008), although mGlu2 KO mice are not reported to have an anxious phenotype (Linden et al, 2005).…”
Section: Implications Of the Observed Strain Differencesmentioning
confidence: 99%
“…Results from transgenic mice point to mGlu2 receptors mediating the effects of the mixed agonist in models of schizophrenia (Fell et al, 2008;Woolley et al, 2008), whereas human tissue studies favor a role for mGlu3 receptors in psychiatric disease (Corti et al, 2007a;Harrison et al, 2008). The mGlu2 receptors also appear to mediate the analgesic effects of mixed agonists (Chiechio et al, 2009), whereas mGlu3 receptors mediate their neuroprotective effects (Corti et al, 2007b), and their anxiolytic activity appears to be mediated by both group II receptors (Linden et al, 2005). However, the initial behavioral observation that the insensitive B&K:Wi strain shows a more anxiety-like profile suggests that the lack of mGlu2 receptors may be one of the factors leading to an anxious phenotype and may suggest that mGlu2 receptors mediate at least some of the anxiolytic actions of mixed mGlu2/3 agonists reported in the clinic (Grillon et al, 2003;Dunayevich et al, 2008), although mGlu2 KO mice are not reported to have an anxious phenotype (Linden et al, 2005).…”
Section: Implications Of the Observed Strain Differencesmentioning
confidence: 99%
“…Recent evidence suggests that the acetylating agent L-acetylcarnitine (LAC), a drug marketed for the treatment of neuropathic pain (9), causes analgesia increasing type 2 metabotropic glutamate (mGlu2) expression via an epigenetic mechanism shared by HDAC inhibitors (10)(11)(12). mGlu2 and its cognate receptor, mGlu3, are coupled to Gi/Go proteins and are preferentially (albeit not exclusively) localized in the preterminal region of axons, where they negatively modulate neurotransmitter release (13).…”
mentioning
confidence: 99%
“…TSA produces analgesia in animal models with an associated decrease in expression of transient receptor potential type-1 cation channel (TRPV1) and protein kinase Ce [157]. SAHA reduces the nociceptive response of animals during the second phase of the formalin test [154]. These drugs increase acetylation of the transcription factor p65/Re1A, which enhances gene expression of the metabotrobic glutamate receptors (mGlu2) in dorsal root ganglia neurons.…”
Section: Intervention: Hdac Inhibitionmentioning
confidence: 99%
“…In neurodegenerative disease, HDACis have been evaluated secondary to their ability to induce neural growth and to improve memory [153]. HDACis have also demonstrated evidence for analgesia in both inflammatory and neuropathic pain [151,154,155]. The clinical effect of many of these drugs is thought to be partially attributed to reduced production of inflammatory cytokines such as TNF-a and IL-1b [156].…”
Section: Intervention: Hdac Inhibitionmentioning
confidence: 99%